EPIDEMIOLOGICAL PROFILE OF HIV POST-EXPOSURE PROPHYLAXIS CONSULTATIONS (2017–2023) - Gurgel Fernandes Távora, Lara; Farias Castelo Branco Eulálio, Tiago; Pereira de Oliveira, Ana Lalessa (Cadernos ESP, 2026)
Objective: To assess the epidemiological profile of HIV PEP consultations at Hospital São José de Doenças Infecciosas from 2017 to 2023. Method: Retrospective study with medical record review and descriptive analysis of epidemiological variables: sex, age, and type of exposure. Results: Of the 29,868 HIV PEP consultations, 66.7% resulted from sexual exposures. Of these, 3.7% involved sexual violence, mostly among females < 18 years old. Consensual sexual exposure (CSE) was the main reason for HIV PEP (64.3%), being more common among men aged 25–29. A steady increase in consultations was observed over the years, both for occupational accidents and for CSE. Final considerations: Demand for HIV PEP has been increasing. The main form of risk exposure is CSE among young men, followed by occupational accidents. These results highlight the importance of expanding access to PEP services, conducting campaigns addressing correct condom use and information about PEP, and providing ongoing training on the prevention of occupational accidents.
Keywords: HIV; Post-Exposure prophylaxis; Prevention